Preparation and Stability of Resveratrol-Loaded Pickering Emulsion Stabilized by Walnut Protein/Cistanche deserticola polysaccharide Composite Nanoparticles - LIU Zhanxia, LI Binbin, ZHAO Yue, WEI Changqing, FU Yini, WANG Ting, WU Hongbin, FU Xizhe (Shipin Kexue)
In this study, walnut protein/Cistanche deserticola polysaccharide (WP/CDPS) composite nanoparticles were constructed and employed as a stabilizer to prepare a Pickering emulsion. The nanoparticles and the Pickering emulsion were evaluated in terms of particle size, polydispersity index and zeta potential. The effect of WP/CDPS mass ratio on the interfacial tension, storage stability, thermal stability, encapsulation efficiency, microstructure and oxidation stability of the Pickering emulsion was investigated. The results showed that with the increase in the proportion of CDPS, the zeta potential of the WP/CDPS nanoparticles gradually decreased from −22 to −37 mV. The Pickering emulsion (C1W1R) with a mass ratio of WP to CDPS of 1:1 had the smallest average particle size (5.927 μm), the lowest interfacial tension (11.88 mN/m), good storage stability and thermal stability. After 480 h of storage, the proportion of the emulsified layer was 95.6%. The particle size of C1W1R had the smallest change with temperature. The results of confocal laser scanning microscopy (CLSM) showed that the WP/CDPS-stabilized emulsion could effectively encapsulate resveratrol (RT) with an encapsulation efficiency of more than 85%, which was higher than that of WP-stabilized emulsion, and the encapsulation efficiency reached 92.9% after 35 days of storage. Pickering emulsions stabilized by WP/CDPS offer a promising alternative carrier for steady-state delivery of resveratrol in the functional food industry and other related industries.